Simulação numérica de junções soldadas sob cargas dinâmicas - Barbosa, Victor Matheus de Farias (2021)
Welding is one of the most important manufacturing processes in engineering today. Used in the oil, naval and civil industries, among others, welding is considered a versatile process, as it promotes the joining of materials in a fast, safe and economical way, when compared to other processes. Although widely used, over the years there was a certain misunderstanding of the behavior of welded joints when subjected to fatigue loads, and many projects did not contemplate details that significantly influenced the failure of components. Thus, this work aims to analyze the fatigue strength of welded structures under dynamic loads using the Finite Element Method (FEM), to evaluate the strength of the welded component, comparing the results obtained with analytical methods. Different types of contacts between the bodies were modeled, and it was observed that the simulation results diverged more from the analytical solution when frictional contact between the plates was used. However, each welded joint must be analyzed separately, to provide a better construction of the model. More accurate results can be achieved if simulations are performed, after validation of some experimental results